Radon Concentration Potential in Bibala Municipality Water: Consequences for Public Consumption - Kessongo, Joaquim (2019)
The primary motivation for this work is the evaluation of the radon concentration in portable water for human consumption in Bibala, a municipality in Angola, where granitic rocks are common, and contain a high concentration of uranium that can be mobilized in underground water. Radon is the largest contributor of radioactive pollution in underground water.Its concentration in water, represents a public health risk due to the fact that the gas can easily escape into the air, adding to the total indoor concentration of radon.On the other hand, ingestion of water with a high radon concentration represents an additional risk to the stomach. Measurements of radon concentration, in Bibala municipality's water, were performed on 16 samples obtained from wells of various depths and analyzed with DURRIDGEs' RAD7 equipment. Measured concentrations are in the range from 39.5 to 202 Bq/L , with 2 of the recovered samples presenting values over 100 Bq/L.